Мускус и камфора. «Отъ меня вечоръ Леила…» А. С. Пушкина: Cтруктура текста и поэтическая традиция [Musk and Camphor. Pushkin´s Poem “Ot menia vechor Leila...”: The Structure of the Text and Poetic Tradition] - Dvinyatin, Fyodor (Slavica Revalensia, 2016)
The article analyzes the structure of one of Alexander Pushkin’s last poems—“Ot menia vechor Leila…” (1835—36): from the level of phonetics to the levels of grammar and lexis. After completing the formal analysis, Fyodor Dvinyatin moves on to the poem’s semantics: he singles out the opposition musk vs. camphor, and focuses on the description of its function in Pushkin’s poem and in poetic tradition.